Cross-cultural adaptation and validation of the Sinhala version of the Hospital Anxiety and Depression Scale (HADS) for patients diagnosed with ischemic heart disease (IHD) in Sri Lanka - C. K. W. Gamage; P. De Zoysa; A. Balasuriya; N. Fernando; D. Jayamanne (College of Community Physicians of Sri Lanka, 2023)
Introduction: The Hospital Anxiety and Depression Scale (HADS) is a frequently used instrument to measure depression and anxiety symptoms among patients diagnosed with ischaemic heart disease (IHD). However, a Sinhala version of HADS for Sri Lankan IHD patients has not been validated in Sri Lanka. Objectives: To translate, cross-culturally adapt and validate the HADS in a Sinhala-speaking Sri Lankan population with IHD Methods: The Sinhala translation of HADS was conducted in four phases: forward translation, backward translation, patient testing and proofreading with the Mapi Research Trust guidelines. Content and consensual validation of the translated scale was conducted with the Delphi method, and the ratings were evaluated for consensus. The validated scale was administered to a sample selected using systematic sampling of 140 IHD patients attending medical clinics at a base hospital in Sri Lanka. Factor structure was verified with Confirmatory Factor Analysis (CFA) and reliability with internal consistency by Cronbach's alpha. Results: The HADS Sinhala version showed good content and consensual validity. CFA proved that the uncorrelated two-factor structure was compatible with the original instrument (x2=156.98; df=76; p<0.001). The Confirmatory Fit Index (CFI) was 0.89, and the Root Mean Square Error of Approximation (RMSEA) was 0.09. The reliability analysis indicated Cronbach's alpha for depression and anxiety as 0.86 and 0.83, respectively. Conclusions & Recommendations: The cross-culturally adapted HADS Sinhala version shows similar psychometric properties as the original instrument and can be used in future studies with confidence.